Human Security dan Politik Kolaboratif Sektor Swasta dalam Pencegahan Perdagangan Manusia (International Forum of Researchers and Lecturers, 2026)
This study examines the role of the private sector in collaborative politics to strengthen human security in preventing human trafficking in Kupang City, East Nusa Tenggara Province. Human trafficking is an extraordinary crime that poses serious threats to human security, particularly for Indonesian Migrant Worker Candidates (CPMI) who are highly vulnerable to exploitation and illegal recruitment. The complexity of this issue requires the involvement of multiple actors, including not only the government but also the private sector. This research employs a qualitative descriptive method, with data collected through interviews, observation, and documentation. The research sites include BP3MI East Nusa Tenggara as a government representative and two private companies, PT Bakti Unggul Sejahtera (PT BUS) and PT AKKA AL-MATAR. The analysis is based on the collaborative governance framework proposed by Ansell and Gash, which emphasizes face-to-face dialogue, trust building, commitment to the process, shared understanding, and intermediate outcomes. The findings indicate that collaboration between the government and the private sector plays a significant role in preventing human trafficking through legal recruitment processes, pre-departure training, capacity building, and supervision of labor placement procedures. Although challenges remain in coordination and policy consistency, these collaborative practices contribute positively to strengthening the protection of migrant workers’ rights and security. This study concludes that collaborative politics between the government and the private sector is a crucial strategy in developing a human security–oriented human trafficking prevention system